Sulfur-doped Fe3O4-FeNi3 / CN double-metal composite catalyst, preparation method thereof and application of sulfur-doped Fe3O4-FeNi3 / CN double-metal composite catalyst
The preparation of sulfur-doped Fe3O4-FeNi3/CN catalyst by preferential sulfur doping, the problem of low crystallinity of FeNi3 catalyst is solved, and efficient oxygen evolution catalytic activity and stability is achieved, which is suitable for the application of oxygen reduction catalysts.
Patent Information
- Application Number
- CN202411517300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the prior art, the crystallinity of the FeNi3 catalyst is not high and is in a metastable structure, making it difficult to effectively improve the performance and stability of its oxygen evolution reaction.
By preferential sulfur doping, a sulfur-doped Fe3O4-FeNi3/CN catalyst is prepared to control the crystallinity of FeNi3 and avoid transitional vulcanization, thereby improving the oxygen evolution catalytic activity of the catalyst.
The high crystallinity of FeNi3 alloy is achieved, and the catalytic activity and stability of the oxygen evolution catalyst is improved, which is specifically manifested as a decrease in overpotential at 10mA cm-2 and a significant decrease in attenuation rate of 50h.
Smart Images

Figure HDA0005107071950000011 
Figure HDA0005107071950000012 
Figure HDA0005107071950000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water oxidation catalyst preparation, and specifically relates to a preparation method, product and application of a sulfur-doped bimetallic composite catalyst. Background Art
[0002] Hydrogen energy has high energy density and environmental friendliness, and is widely regarded as a promising energy carrier for achieving energy upgrading. Among various hydrogen production technologies, electrocatalytic water splitting stands out due to its multiple advantages such as zero pollution, high product purity, and simple operation. Generally speaking, water splitting involves two half reactions: anodic oxygen evolution reaction (OER) and cathodic hydrogen evolution reaction (HER). Compared with HER, OER has higher energy requirements and thermodynamic barriers due to its slow multi-proton coupled electron transfer process. Although noble metal-based electrocatalysts (such as RuO2 and IrO2) have shown impressive activity in OER, their widespread application is hindered by their scarcity and durability. Therefore, there is an urgent need to construct earth-abundant transition metal-based electrocatalysts to replace noble metal-based electrocatalysts, so as to take a step towards large-scale water splitting hydrogen production.
[0003] So far, people have been committed to developing non-precious metal OER catalysts with excellent performance and low price. Compounds such as Cr, Co, and Fe are considered to be high-value candidates for improving the activity of oxygen evolution reaction. Among non-precious metal catalysts, Ni-based and Fe-based catalysts have attracted much attention due to their abundant world reserves. In recent years, combining two or more catalytic materials to construct heterostructures has become an effective strategy to improve the activity of catalysts. The formation of heterostructures can not only effectively promote interfacial electron transport and regulate the adsorption free energy of reaction species, but also produce new interfacial structures by changing the composition and crystal phase of the structure, thereby achieving efficient oxygen evolution catalytic function. In addition, the preparation of multi-component transition metals (such as Co, Ni, and Fe) by element doping is also a good engineering strategy. By controlling and designing defect engineering to regulate active centers, great success has been achieved, showing good electrocatalytic activity, thereby improving the oxygen evolution activity of OER.
[0004] The purpose of adding sublimated sulfur for pyrolysis in this field is to generate sulfides. The present invention studies the effect of sulfur on the crystallinity of FeNi3 for the first time. When the catalyst is not doped with sublimated sulfur, the prepared FeNi3 has low crystallinity and is in a metastable structure. The purpose of adding sublimated sulfur is not only to improve the adsorption effect of the electrode material, but also to improve the crystallinity of FeNi3 in the catalyst, thereby optimizing the performance and stability of its oxygen evolution reaction. In the preparation process, how much sublimated sulfur is added to ensure that the crystallinity of FeNi3 increases while it will not be transitionally sulfurized into sulfides is the main problem that needs to be solved at present. Therefore, this paper studies different amounts of sublimated sulfur to explore the best optimization ratio to improve the crystallinity of FeNi3 alloy in the catalyst, which has not been reported in related research. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing a sulfur-doped bimetallic composite catalyst. By optimizing the amount of sulfur, it is ensured that the crystallinity of FeNi3 is increased while it will not be oversulfurized to sulfide, thereby improving the oxygen evolution catalytic activity of the catalyst.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a sulfur-doped Fe3O4-FeNi3 / CN catalyst, comprising:
[0008] (1) Weigh iron nitrate, nickel nitrate and sublimed sulfur in an ethanol solvent, mix them, and stir them evenly with a magnetic stirrer to obtain a yellow solution.
[0009] (2) Weigh polyaniline and place it in the yellow solution, stir it evenly and then dry it, and then calcine the obtained black substance at high temperature to obtain Fe3O4-FeNi3-S / CN catalyst
[0010] The molar ratio of iron nitrate to nickel nitrate is 3:1 to 1:3, and the calcination temperature is 500° C. More preferably, the molar ratio of iron nitrate to nickel nitrate is 1:1.
[0011] The total molar amount of metal and the mass ratio of polyaniline are 2mmol:0.2g. Polyaniline not only serves as a dispersion medium and carrier, but also protects and reduces metals. During high-temperature calcination, polyaniline will generate reducing gases such as NO and CO, which will cause the metal ions embedded in it to undergo a reduction reaction, making them partially exist in an alloy state. In addition, polyaniline after high-temperature calcination also protects active metals and improves reaction stability.
[0012] The high temperature pyrolysis temperature is 400-700°C, the pyrolysis time is 3 hours, and the pyrolysis atmosphere is nitrogen. The high temperature pyrolysis temperature is more preferably 500°C.
[0013] The molar ratio of the total molar amount of metal to the sublimated sulfur is 2:0.5 to 2. More preferably, the molar ratio of the total molar amount of metal to the sublimated sulfur is 2:1.
[0014] When the amount of sublimated sulfur is lower than the molar ratio of the total molar amount of metal to sublimated sulfur of 2:1, the optimization degree of the catalyst does not reach the best, and the crystallinity of the FeNi3 alloy is not improved to the maximum extent; when the amount of sublimated sulfur is higher than this amount, the FeNi3 alloy will be sulfurized by excessive sublimated sulfur, causing the FeNi3 alloy to disappear and the oxygen evolution catalytic activity to decrease.
[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a product obtained by a method for preparing a bimetallic composite catalyst Fe3O4-FeNi3 / CN.
[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a sulfur-doped bimetallic composite catalyst Fe3O4-FeNi3-S / CN, and to use the product as an oxygen reduction catalyst.
[0017] Beneficial effects of the present invention:
[0018] The present invention provides a method for preparing a sulfur-doped bimetallic composite catalyst Fe3O4-FeNi3 / CN, wherein ferric nitrate, nickel nitrate and polyaniline are compounded with sublimated sulfur to achieve a good synergistic catalytic effect; by optimizing the compounding ratio, the effects of the molar amount of ferric nitrate and nickel nitrate and the calcination temperature on the catalyst are investigated; then, by introducing sublimated sulfur into the raw materials, a Fe3O4-FeNi3-S / CN series catalyst is prepared, and the effect of the amount of sublimated sulfur on the catalyst structure and performance is mainly investigated. The main crystalline phase structure of the prepared catalyst is FeNi3 and Fe3O4, and as the amount of sublimated sulfur gradually increases, the FeNi3 crystalline phase shown in the XRD spectrum shows a trend of first increasing and then decreasing. The activity of the catalyst also increases with the increase of the FeNi3 crystalline phase. Among them, the Fe1Ni1-S1 / PANI-500 catalyst has the best crystallinity and the best oxygen evolution catalytic activity, at 10 mA cm -2 Under this condition, the overpotential is only 336mV and the decay rate is only 1.6% in 50h. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0020] Figure 1 The XRD comparison diagram of the catalysts in Examples 1, 3, and 5 of the present invention is shown.
[0021] Figure 2 It is the XRD comparison diagram of the catalysts in Examples 1, 2 and 14 of the present invention.
[0022] Figure 3 This is a LSV comparison diagram of samples with different metal molar ratios in Examples 1, 3, 4, 5, and 6 of the present invention.
[0023] Figure 4 This is a comparison chart of LSV of samples at different temperatures in Examples 1, 7, 8, and 9 of the present invention.
[0024] Figure 5 This is a LSV comparison diagram of samples with different sulfur contents in Examples 2, 10, 11, 12, 13, and 14 of the present invention.
[0025] Figure 6 The samples in Examples 1, 2, and 10 of the present invention were subjected to 10 mA cm -2 The Vt curve after 50h test is shown below. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] Evaluation of water oxidation reaction performance in the embodiments of the present invention:
[0030] Tested by electrochemical workstation:
[0031] First, polish the glassy carbon electrode (area 0.126 cm) with a small amount of 1 μm aluminum oxide polishing powder. 2) until its surface is bright, and then rinse with deionized water and ethanol, and dry in the shade at room temperature. Weigh 2 mg of catalyst and 2 mg of activated carbon (to improve accuracy) and put them into a sample tube, add 950 μL of anhydrous ethanol and 50 μL of Nafion solution, and obtain a uniformly dispersed ink after ultrasonic treatment. Then take 15.8 μL of ink and drop it on the surface of the glassy carbon electrode, dry in the shade at room temperature for use. The loading amount of catalyst on the electrode surface is 0.25 mg cm -2 ;
[0032] In 1 mol L -1 The electrochemical performance of the catalyst at room temperature was tested in a three-electrode system of KOH solution. The glassy carbon electrode (GC) loaded with the catalyst was used as the working electrode, the Ag / AgCl electrode saturated with KCl was used as the reference electrode, and the carbon rod was used as the counter electrode.
[0033] The RDE speed of the LSV test is 1600 rpm, the test voltage range is -0.023 to 0.977 V, and the scan rate is 5 mV s -1 .
[0034] The LSV polarization curve can be used to obtain important parameters of OER catalyst performance: 10 mA cm -2 Overpotential at current density.
[0035] The Vt constant current curve can be used to obtain the catalyst attenuation rate after long-term testing.
[0036] At 10 mA cm -2 The lower the overpotential under current density, the smaller the decay rate after long-term testing, indicating that the catalyst has a higher electrocatalytic water oxidation activity.
[0037] The raw materials in the embodiments of the present invention are all common commercially available products.
[0038] Example 1
[0039] Preparation and testing of polyaniline materials:
[0040] (1) Weigh 20 mmol of aniline and place it in a beaker. Pour 50 mL of 2 mol L -1 HCl, and stir evenly with a magnetic stirrer, and cool to 0-5°C in an ice-water mixture to obtain a colorless solution A;
[0041] Weigh 20 mmol of ammonium persulfate and place it in a beaker. Pour 50 mL of deionized water into the beaker and stir evenly with a magnetic stirrer to obtain a colorless and transparent solution B.
[0042] Place solution B in a constant pressure funnel and, at 0-5°C, add 1 mL / min -1Slowly add dropwise to solution A at a speed of , while continuing to stir solution A, and obtain green solution C after 6 hours;
[0043] Then, solution C was centrifuged and washed three times with anhydrous ethanol, and the green precipitate was collected and dried in a vacuum drying oven at 60°C overnight;
[0044] The obtained green product is put into an agate mortar and ground evenly, and the obtained green powder is polyaniline.
[0045] (2) Preparation of Fe3O4-FeNi3 / CN materials:
[0046] Weigh 1 mmol of ferric nitrate and 1 mmol of nickel nitrate into a beaker, so that the total molar weight of the metals is 2 mmol. Pour 20 mL of methanol into the beaker and stir evenly with a magnetic stirrer to obtain a yellow solution D.
[0047] Weigh 200 mg of polyaniline into the yellow solution D and stir with a magnetic stirrer for 3 h to obtain a black solution E;
[0048] Place solution E in a 60°C water bath and dry completely to obtain black powder F;
[0049] Then, the black powder F was placed in a tubular furnace under a nitrogen atmosphere at 500° C. and calcined for 3 h to obtain a black product G;
[0050] The obtained black product G was put into an agate mortar and ground evenly to obtain a black powder, namely Fe3O4-FeNi3 / CN. The final product was named Fe1Ni1 / PANI-500.
[0051] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 , Figure 6 ;
[0052] It can be seen that the Fe1Ni1 / PANI-500 catalyst has the highest electrocatalytic water oxidation performance. -2 The overpotential under the condition is 336 mV, and the decay rate after 50 h is 4.1%.
[0053] Example 2
[0054] Preparation of Fe3O4-FeNi3-S / CN material:
[0055] Weigh 1 mmol of ferric nitrate, 1 mmol of nickel nitrate, and 1 mmol of sublimed sulfur into a beaker, pour 20 mL of methanol into the beaker, and stir evenly with a magnetic stirrer to obtain a yellow solution①.
[0056] Weigh 200 mg of polyaniline into the yellow solution ① and stir with a magnetic stirrer for 3 h, then put it into a 60°C water bath to dry completely, and calcine the obtained black substance in a tubular furnace under a nitrogen atmosphere at 500°C for 3 h to obtain a black product ②;
[0057] The obtained black product ② was put into an agate mortar and ground evenly to obtain a black powder, namely Fe3O4-FeNi3-S / CN. The final product was named Fe1Ni1-S1 / PANI-500.
[0058] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 , Figure 6 ;
[0059] It can be seen that the Fe1Ni1-S1 / PANI-500 catalyst has the highest electrocatalytic water oxidation performance. -2 The overpotential under the condition is 298 mV, and the decay rate after 50 h is 1.6%.
[0060] Example 3
[0061] Preparation of Fe3O4-FeNi3 / CN material with a molar ratio of ferric nitrate to nickel nitrate of 2:1:
[0062] The same synthesis method was used as in Example 1, except that the molar amounts of iron nitrate and nickel nitrate were changed to 1.3 mmol and 0.7 mmol, respectively, and the other molar amounts remained unchanged. The final product was named Fe2Ni1 / PANI-500.
[0063] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 , Fe2Ni1 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 388 mV.
[0064] Example 4
[0065] Preparation of Fe3O4-FeNi3 / CN material with a molar ratio of ferric nitrate to nickel nitrate of 3:1:
[0066] The same synthesis method was used as in Example 1, except that the molar amounts of ferric nitrate and nickel nitrate were changed to 1.5 mmol and 0.5 mmol, respectively, and the other molar amounts remained unchanged. The final product was named Fe3Ni1 / PANI-500.
[0067] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 , Fe3Ni1 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2The overpotential is 540 mV.
[0068] Example 5
[0069] Preparation of Fe3O4-FeNi3 / CN material with a molar ratio of ferric nitrate to nickel nitrate of 1:2:
[0070] The same synthesis method was used as in Example 1, except that the molar amounts of iron nitrate and nickel nitrate were changed to 0.7 mmol and 1.3 mmol, respectively, and the other molar amounts remained unchanged. The final product was named Fe1Ni2 / PANI-500.
[0071] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 , Fe1Ni2 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 407 mV.
[0072] Figure 1 The XRD comparison diagram of the catalyst in Examples 1, 3, and 5 of the present invention shows that the two crystal forms belonging to the catalyst are as follows: the diffraction peaks at 2θ of 18.9°, 30.8°, 35.4°, 43.1°, 53.6°, 57.0°, and 62.3° are all attributed to the (111), (220), (311), (400), (422), (511), and (440) crystal planes of Fe3O4 (PDF#87-2337); and the diffraction peaks at 2θ of 44.4°, 51.8°, and 76.2° correspond to the (111), (200), and (220) crystal planes of FeNi3 (PDF#99-0073), respectively. This indicates that Fe3O4 and FeNi3 exist in the catalyst at the same time. Among these catalysts, as the proportion of nickel element usage gradually increases, the peak shape of the characteristic diffraction peak of FeNi3 gradually becomes sharper, and the peak shape of the characteristic diffraction peak of Fe3O4 gradually becomes broader. When the nickel element usage is 1mmol, the peak intensity of the characteristic diffraction peak of FeNi3 is the largest. In addition, no obvious diffraction peak of carbon derived from polyaniline is seen in the XRD spectrum. This is because its peak intensity is low, making it difficult to detect.
[0073] Example 6
[0074] Preparation of Fe3O4-FeNi3 / CN material with a molar ratio of ferric nitrate to nickel nitrate of 1:3:
[0075] The same synthesis method was used as in Example 1, except that the molar amounts of iron nitrate and nickel nitrate were changed to 0.5 mmol and 1.5 mmol, respectively, and the other molar amounts remained unchanged. The final product was named Fe1Ni3 / PANI-500.
[0076] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 , Fe1Ni3 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 535mV.
[0077] Example 7
[0078] Preparation and testing of Fe3O4-FeNi3 / CN catalyst calcined at 400°C:
[0079] The same synthesis method was used as in Example 1. The calcination temperature of Fe1Ni1 / PANI-T was 400°C, and the other parameters remained unchanged. The final product was named Fe1Ni1 / PANI-400.
[0080] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 , Fe1Ni1 / PANI-400 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 505mV.
[0081] Example 8
[0082] Preparation and testing of Fe3O4-FeNi3 / CN catalyst calcined at 600°C:
[0083] As in Example 1, the same synthesis method was adopted, the calcination temperature of Fe1Ni1 / PANI-T was 600°C, and the other parameters remained unchanged. The final product was named Fe1Ni1 / PANI-600.
[0084] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 , Fe1Ni1 / PANI-600 electrocatalytic water oxidation at 10 mA cm -2 The overpotential under is 369mV.
[0085] Example 9
[0086] Preparation and testing of Fe3O4-FeNi3 / CN catalyst calcined at 700°C:
[0087] The same synthesis method was used as in Example 1. The calcination temperature of Fe1Ni1 / PANI-T was 700°C, and the other parameters remained unchanged. The final product was named Fe1Ni1 / PANI-700.
[0088] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 , Fe1Ni1 / PANI-700 electrocatalytic water oxidation at 10 mA cm -2The overpotential is 401mV.
[0089] Example 10
[0090] Preparation and testing of Fe3O4-FeNi3-S / CN catalyst with sulfur dosage of 0.5 mmol:
[0091] The same synthesis method was used as in Example 2, the sublimation dosage was 0.5 mmol, and the other parameters were unchanged. The final product was named Fe1Ni1-S 0.5 / PANI-500.
[0092] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 , Figure 6 ,Fe1Ni1-S 0.5 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential under the condition is 322mV, and the decay rate after 50h is 3.0%.
[0093] Embodiment 11
[0094] Preparation and testing of Fe3O4-FeNi3-S / CN catalyst with sulfur dosage of 0.75 mmol:
[0095] The same synthesis method was used as in Example 2, the sublimation dosage was 0.75 mmol, and the other parameters were unchanged. The final product was named Fe1Ni1-S 0.75 / PANI-500.
[0096] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ,Fe1Ni1-S 0.75 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 317 mV.
[0097] Example 12
[0098] Preparation and testing of Fe3O4-FeNi3-S / CN catalyst with sulfur dosage of 1.25 mmol:
[0099] The same synthesis method was used as in Example 2, the sublimation dosage was 1.25 mmol, and the other parameters were unchanged. The final product was named Fe1Ni1-S 1.25 / PANI-500.
[0100] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ,Fe1Ni1-S 1.25 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 303 mV.
[0101] Example 13
[0102] Preparation and testing of Fe3O4-FeNi3-S / CN catalyst with sulfur dosage of 1.5 mmol:
[0103] The same synthesis method was used as in Example 2, the sublimation dosage was 1.5 mmol, and the other parameters were unchanged. The final product was named Fe1Ni1-S 1.5 / PANI-500.
[0104] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ,Fe1Ni1-S 1.5 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 314 mV.
[0105] Embodiment 14
[0106] Preparation and testing of Fe3O4-FeNi3-S / CN catalyst with 2 mmol sulfur dosage:
[0107] The same synthesis method was used as in Example 2, the sublimation dosage was 2 mmol, and the other parameters remained unchanged. The final product was named Fe1Ni1-S2 / PANI-500.
[0108] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 , Fe1Ni1-S2 / PANI-500 electrocatalytic water oxidation at 10 mA cm -2 The overpotential is 344 mV.
[0109] XRD comparison diagrams of Fe1Ni1 / PANI-500, Fe1Ni1-S1 / PANI-500 and Fe1Ni1-S2 / PANI-500 prepared in Examples 1, 2 and 14 of the present invention are shown in FIG. Figure 2 It can be seen that when 1 mmol sulphur dioxide is added to the catalyst for sulphurization, the diffraction peak belonging to FeNi3 becomes sharper, and the peak intensity of the diffraction peak increases significantly, the crystallinity increases, and the transition from metastable structure to highly stable structure is achieved. When 2 mmol sulphur dioxide is added for sulphurization, the catalyst presents a state of transitional sulphurization, the diffraction peak belonging to FeNi3 almost disappears, and the diffraction peaks of by-products Ni3S2 and (Fe,Ni)9S8 appear instead. In the oxygen evolution electrochemical test, when the current density is 10 mA cm -2When the overpotential of Fe1Ni1 / PANI-500, Fe1Ni1-S1 / PANI-500 and Fe1Ni1-S2 / PANI-500 was 336mV, 298mV and 344mV respectively, indicating that in this system, the appropriate amount of sulfurization will increase the crystallinity of FeNi3 in the catalyst, which is conducive to the improvement of oxygen evolution activity. The consequence of the transitional sulfurization of the catalyst is the appearance of byproducts Ni3S2 and (Fe, Ni)9S8, which leads to a decrease in the catalytic activity of the catalyst. And when the sulfur dosage is greater than 1mmol, the performance of the catalyst decays, which is due to excessive sulfurization, FeNi3 reduction, and an increase in byproducts.
[0110] The Fe1Ni1 / PANI-500 and Fe1Ni1-S prepared in Examples 1, 2, and 10 of the present invention 0.5 / PANI-500, Fe1Ni1-S1 / PANI-500 in 1 mol L -1 KOH (10 mA cm -2 ) 50h constant current test comparison chart, see Figure 5 After the amount of sulfur dioxide in the catalyst Fe1Ni1 / PANI-500 was gradually increased to 1 mmol, the catalyst attenuation rate dropped from 4.1% to 1.6%, and the catalytic stability was significantly improved.
[0111] The invention compounds ferric nitrate, nickel nitrate, sublimated sulfur and polyaniline to achieve a good synergistic catalytic effect; at the same time, the compounding ratio and calcination temperature are optimized to achieve the best water oxidation performance.
[0112] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst, characterized in that: The black solid mixture is prepared by mixing polyaniline with iron salt, nickel salt and sublimed sulfur, and then pyrolyzed at high temperature to obtain Fe3O4-FeNi3-S / CN catalyst; The molar ratio of the iron salt to the nickel salt is 3:1 to 1:3; the molar ratio of the total metal of the iron salt and the nickel salt to the sublimated sulfur is 2:0.5 to 2.
2. The method for preparing the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst according to claim 1, characterized in that: The preparation steps are as follows: (1) dissolving iron salt, nickel salt and sublimed sulfur in an alcohol solvent and stirring to obtain a solution A; (2) dispersing polyaniline in solution A and stirring to obtain a black suspension solution B; (3) The black suspension solution B is dried and then pyrolyzed at 400-700°C in a tube furnace to obtain Fe3O4-FeNi3-S / CN.
3. The method for preparing the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst according to claim 2, characterized in that: The iron salt is iron nitrate; the nickel salt is nickel nitrate; and the molar ratio of iron nitrate to nickel nitrate is 1:
1.
4. The method for preparing the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst according to claim 2, characterized in that: The molar ratio of the total metal moles of the iron salt and the nickel salt to the sublimated sulfur is 2:
1.
5. The method for preparing the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst according to claim 2, characterized in that: The high temperature pyrolysis temperature is 500°C, the pyrolysis time is 3h, and the pyrolysis atmosphere is nitrogen.
6. The method for preparing the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst according to claim 2, characterized in that: The total metal molar amount of the iron salt and the nickel salt to the mass ratio of the polyaniline is 2mmol:0.2g.
7. A sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst prepared by the method according to any one of claims 1 to 6.
8. Use of the sulfur-doped Fe3O4-FeNi3 / CN bimetallic composite catalyst prepared by the method according to any one of claims 1 to 6 in oxygen evolution by water electrolysis.
Citation Information
Patent Citations
FeNi3 composite nitrogen-doped carbon nanotube bifunctional electrocatalyst prepared from biomass
CN114420959A
Transition metal sulfide (Fe, Ni) 9S8-Ni3S2 composite catalyst as well as preparation method and application thereof
CN117443411A
Bifunctional electrocatalyst for water splitting and preparation method thereof
WO2017091955A1